Increased left ventricular mass as a marker of left ventricular hypertrophy in normotensive type 2 DM patients - Moustafa Kamal Eldin Ibrahim Khalil Saad; Mohamed Saleh Gomaa; Abdelrahman Ahmed Ewais; Maher Abobaker Alamir; Mohamed Shaban Hashem Mahmoud (The Egyptian Journal of Internal Medicine)
Abstract Background Diabetes is considered to be one of the most important metabolic conditions causing left ventricular (LV) dysfunction, one of which is Left ventricular hypertrophy (LVH). Increased left ventricular mass (LVM) and left ventricular mass index (LVMI) are significant predictors of LVH. Aim This study aims to illustrate the significance of using echocardiography to detect left ventricular hypertrophy (as a type of LV dysfunction) in normotensive patients with type 2 diabetes mellitus. Materials and methods The study included 100 participants who were distributed into two groups: group A included normotensive patients with type 2 DM and group B included normotensive non-diabetic patients as a control group. Results LVM values were significantly higher in group A patients compared to group B (187.11 ± 60.83 vs. 119.15 ± 41.87, p < 0.001). Also, LVMI values were significantly higher in group A in comparison to group B (96.64 ± 29.84 vs. 63.17 ± 20.38, p < 0.001). The proportion of abnormal LVMI was higher in group A than group B (56% vs. 6%, p < 0.001). There was a statistically significant positive correlation between LVM and several study parameters including disease duration (r = 0.369, p = 0.008), FBS (r = 0.478, p < 0.001), 2HPP (0.400, p = 0.004), HA1C (%) (r = 0.589, p = 0.003), LVEDD (r = 0.790, p < 0.001), LVESD (r = 0.388, p = 0.005), SWT (r = 0.897, p < 0.001), PWT (r = 0.808, p < 0.001), and LA (r = 0.322, p = 0.022). Conclusion Left ventricular mass was found to be significantly higher in normotensive type 2 DM patients in comparison to the normotensive non-diabetic control group. LVM is a good marker of LVH among normotensive diabetics and significantly correlates with DM control and duration.